Identity of entrepreneur teachers: a narrative inquiry in activity theory lenses - Ari Primantoro, Leonardus Bayu ((JELE) Journal Of English Language and Education, 2018)
This[D1] paper aims to provide readers with a useful introduction to Activity Theory, focusing on the implementation of the theory towards analysis of teacher identity construction in relation to entrepreneurship. The research was conducted[D2] to analyze the phenomenon about teachers who also work as entrepreneur focusing on their identity construction or transformation.  The research[D3] itself is a qualitative research using narrative inquiry as data gathering technique.Based on the 2 respondents analyzed[D4] , it can be concluded that the respondents has already had a strong identity as a teacher formed by their environment, community, tools, rules, and objectives before they decided to start being entrepreneur. The entrepreneurship itself is formed as one shape of the respondents’ agency in teaching. Hence, one of the implications of the research is that in order to form teachers who have strong agency, a teacher training institution must start to form the identity of its students as early as possible. keywords: activity theory, narrative inquiry, teacher identity, entrepreneur, agency